2018
DOI: 10.1021/acs.joc.8b00229
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Decarboxylative C–H Alkenylation in Aqueous Media: Synthesis of Tetrahydropyridoindoles

Abstract: We disclose herein a Ru(II)-catalyzed decarboxylative and oxidative coupling of N-substituted indolyl carboxylic acids with broad substrate scope in an aqueous solution. This method provides a sustainable and efficient access to synthesize various indole-fused cyclohexanyl acetic acids under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 69 publications
1
7
0
1
Order By: Relevance
“…), 46.4 (NCH 2 ), 30.8 (CH 2 ), 28.9 (CH 2 ); v max 3336, 2979, 1537, 1515, 1447, 1425, 1401, 1383, 1362, 1274, 1171, 1118, 1030, 994, 920, 872, 836, 802, 782, 758, 623, 563, 544, 507; HRMS (ESI+) C 14 H 15 NO 2 [M + H] + exact mass 230.1181, accurate mass 230.1181 (mass error 2.01 ppm). All physical and spectral properties were consistent with those previously described 32,33 …”
Section: Methodssupporting
confidence: 73%
“…), 46.4 (NCH 2 ), 30.8 (CH 2 ), 28.9 (CH 2 ); v max 3336, 2979, 1537, 1515, 1447, 1425, 1401, 1383, 1362, 1274, 1171, 1118, 1030, 994, 920, 872, 836, 802, 782, 758, 623, 563, 544, 507; HRMS (ESI+) C 14 H 15 NO 2 [M + H] + exact mass 230.1181, accurate mass 230.1181 (mass error 2.01 ppm). All physical and spectral properties were consistent with those previously described 32,33 …”
Section: Methodssupporting
confidence: 73%
“…Ji and co‐workers disclosed a Ru(II)‐assisted intramolecular decarboxylative C−H alkenylation of N‐substituted indolyl carboxylic acids to access structurally useful indole‐fused cyclohexanyl acetic acids in aqueous media in 2018 (Scheme 17). [29] Optimization study revealed that the promising result was obtained when molecular oxygen was employed as an oxidant to catalyze these decarboxylative C−H functionalizations. The reaction proceeded in the presence of Cs 2 CO 3 in aqueous media under oxygen, leading to the formation of the cyclized product up to 79% yield.…”
Section: Intramolecular C−c Bond Formationmentioning
confidence: 99%
“…[13] To access the structurally useful indole-fused cyclohexanyl acetic acids, in 2018, Liu et al reported the ruthenium-catalyzed decarboxylative CÀ H alkenylation in aqueous media (Scheme 5). [14] Indole-3-carboxylic acid moiety was introduced as a traceless directing group that might stabilize the seven-membered cyclo ruthenium intermediate. This method provides a sustainable and efficient access to various indole-fused cyclohexanyl acetic acids under mild conditions.…”
Section: Indole Alkenylationmentioning
confidence: 99%